Searching the effect of anodization process as a surface treatment - Mehmet Coşkun; Burcu Çırak; Türker Akar (Cumhuriyet University, 2018)
Objective: The aim of this study was to compare the effect of anodization and air-particle abrasion surface treatments on shear bond strength between Ni-Cr and ceramics.Material and Methods: 30 cylindrical Ni-Cr specimens (7x10 mm) were divided into three groups according to the surface treatments [control group (no-treatment), air-particle abrasion group (110 µm Al2O3at 75 psi from 20 cm for 30 seconds), and anodization group]. One sample from each group was evaluated by using SEM. Ceramics with a dimension (5x3 mm) built-up on specimens and shear bond strength tests were performed by using universal testing machine with a 1 mm/min crosshead speed. Stereomicroscope was used to evaluate the failure mode of specimens. One-way ANOVA with post-hoc Tukey's test was used to analyze the differences in shear bond strength values.Results: The shear bond strength of air-particle abrasion (21,35∓4,64) was higher than anodization group (20,92∓4,85) however, no statistically significant difference was detected. Both groups showed higher bond strength than control group (8,02∓1,47).Conclusion: Anodization process can be used in order to increase the metal-ceramic bond strength. However, according to the failure mode, air-particle abrasion forms stronger bond strength than anodization.